Cardiopulmonary resuscitation. Paper 2: A survey of basic life support training for medical students. Issue 3 (September 1994) - Graham, C A; Guest, K A; Scollon, D
Abstract : This paper presents the results of a survey of Basic Life Support (BLS) training, based on experience gained by undergraduate medical students who had just completed their first clinical year (third year) at the University of Glasgow. Data were collected on the amount and quality of BLS training received, along with students' own perceptions of their confidence in providing BLS in a cardiac arrest resuscitation attempt. The results made interesting, but not surprising, reading with only 15% of students appearing to have been adequately taught BLS at any point during their third year. Students want more training and 98% see resuscitation as an important topic in the curriculum. Self-perceived confidence in performing BLS in an acute resuscitation situation is low. With no evidence to suggest that the situation is any different elsewhere in the UK, it is recommended that undergraduate resuscitation training is improved to reflect the importance that medical students attach to it.